Numerical simulations of radiative heat effects in a plasma wind-tunnel flow under Mars entry conditions. (October 2018) - García-Garrido, Javier; Pudsey, Adrian S.; Mundt, Christian
Abstract: The Mars atmosphere, consisting mainly of CO2, with a few percent of N2 and other trace gases, is of interest to future space projects. Entry into its gaseous shell is of current significant research interest. For this application, an arc jet driven plasma wind tunnel is available to simulate relevant entry conditions for the planet. Recent improvements and qualification of the test facility, enables the testing on earth of high enthalpy flows with CO2 rich compositions. In order to complement the experimental analysis, numerical simulations of the test facility running at relevant ambient pressures of 600–1000 Pa, corresponding to low altitudes, have been completed. The simulations used a density-based Navier Stokes solver and non-equilibrium chemical and thermal effects which are characteristic of these types of high enthalpy flows. Special interest is given to the radiative heat transfer mechanism. Under these high temperature conditions, radiative effects become more relevant and advanced radiation models must be used. The coupling between the Navier Stokes and radiative transfer equations favours the understanding of plasma wind tunnel flows. The radiative heat is estimated using the k-distribution spectral model, which is appropriate for non-homogeneous radiating media. The numerical results and measurements are compared in order to improve the analysis methods for Mars entry flows. Highlights: Simulation of plasma wind-tunnel flow under Mars conditions. Comparison between two different CFD codes, US3D and NSMB. Validation of numerical results against measurements. Advanced radiative spectral model implemented successfully. Low influence of radiation effects under the plasma wind-tunnel analysed conditions.